2021
DOI: 10.28991/cej-2021-03091750
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Length and Percent Dosage of Recycled Steel Fibers on the Mechanical Properties of Concrete

Abstract: The global rapid increase in waste tyres accumulation, as well as the looming social and environmental concerns, have become major threats in recent times. The use of Recycled Steel Fiber (RSF) extracted from waste tyres in fiber reinforced concrete can be of great profitable engineering applications however the choice of suitable length and volume fractions of RSF is presently the key challenge that requires research exploration. The present experimental work aims at investigating the influence of varying len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…This confirmed that decreasing the diameter of RSF for the same percentage of RSF could cause an inevitable decrease for the same concrete mixture. A similar decrease in FS for reducing the length of the fibers was supported by results reported for specimens 12 to 16 [ 46 ]. On the other hand, an incline of 35% was reported in FS, when 2% of small-size 13 mm long RSF had a diameter of 0.20 mm were incorporated in specimen 12 [ 59 ].…”
Section: The Properties Of Rsf-incorporated Concretesupporting
confidence: 87%
See 4 more Smart Citations
“…This confirmed that decreasing the diameter of RSF for the same percentage of RSF could cause an inevitable decrease for the same concrete mixture. A similar decrease in FS for reducing the length of the fibers was supported by results reported for specimens 12 to 16 [ 46 ]. On the other hand, an incline of 35% was reported in FS, when 2% of small-size 13 mm long RSF had a diameter of 0.20 mm were incorporated in specimen 12 [ 59 ].…”
Section: The Properties Of Rsf-incorporated Concretesupporting
confidence: 87%
“…The maximum enhancement of 68 percent was noted in CS with 2% RSF, 29 mm long, and 0.20 mm thick [ 58 ]. Interestingly, Graeff et al [ 59 ] and Gul et al [ 46 ] reported an increase in CS for RSF with a minimum length of 13 mm and 7.62 mm, respectively. It can be deduced that an increase in CS can be achieved for the exact content of the RSF for varying dimensions of RSF.…”
Section: The Properties Of Rsf-incorporated Concretementioning
confidence: 99%
See 3 more Smart Citations